The use of military strategy in network-centric warfare - Beriša Hatidža (Војно дело, 2020)
The period after the end of the Cold War and the reorganization of the world order brought new challenges to modern military organizations. Total technological progress and completely new threats and opponents in the form of nonlinearity have influenced modern warfare to change its shape and form to such an extent that most theorists believe that we are witnessing revolutionary changes in the character of war. The development of information technology particularly influences the development of new concepts of the use of the armed forces, with the most technologically advanced countries naturally leading the way. The development of information technology has a huge impact on the modernization and transformation of the armed forces, primarily in the West. In order to achieve a qualitatively new, higher level of precision and higher speed in conducting military operations, in the early 1990s, many segments of the US armed forces were specially equipped with modern technology, which is based on information networks. The revolution in military affairs and its implementation in the concept of network-centric warfare have become new military strategic models for the US armed forces, along with the process of redefining security policy, in line with the new situation. Network-centric warfare has set new standards in warfare, relying on information superiority. In this paper, the relation of military strategy and its principles to network-centric warfare is considered.